GIVING AND CHECKING INSTRUCTIONS SKILLS AMONG FOURTH-YEAR STUDENTS DURING THEIR PRACTICUM - Đinh, Thị Hà Phương (2020)
As one of the first attempts to investigate giving and checking instructions skills among fourth-year students during their practicum at college levels, the paper aims at exploring teacher trainees‟ perception of effective instructions and the level of effectiveness with respect to time, speech modification and techniques. To fulfill this primary aim, both qualitative and quantitative methods with three research instruments including observations, questionnaires and interviews were adopted. The participants of the study were 25 fourth-year students of Fast-Track Program and nine supervising teachers from English Division I, at the Faculty of English Language Teacher Education, University of Languages and International Studies, Vietnam National University. The most significant finding of the research was that the language for instructions was the most problematic issue among the trainee teachers. Other difficulties included time and techniques for giving instructions as well as checking students‟ understanding. The paper, therefore, would serve as a good reference for both pre-service and in-service teachers who desire to have a closer look at this issue or to improve their giving and checking instructions skills.